Recognizing Indigenous Knowledges: The Imperative of Decolonization in Higher Education in Chile (International Journal of Multidisciplinary Perspectives in Higher Education, 2025)
This reflection explores the critical importance of decolonization in higher education, emphasizing the recognition and integration of Indigenous knowledges and epistemologies into teacher education courses. Drawing from a critical conversation with a Chilean academic deeply engaged in decolonial practices, the discussion highlights how traditional Western-centric models of education have historically marginalized Indigenous perspectives, leading to a narrow and incomplete understanding of knowledge. The academic highlights the necessity of challenging these dominant paradigms by acknowledging and valuing the rich, diverse epistemologies that Indigenous communities contribute to helping us read the world (Freire & Macedo, 1987) through different onto-epistemological lenses. This process of decolonization is not merely an academic exercise but a transformative approach that seeks to create a more inclusive and equitable educational landscape that is sensitive to diverse voices, perspectives, ways of knowing and being. By integrating Indigenous knowledges, higher education institutions can foster a more holistic and diverse intellectual environment, ultimately contributing to the broader goals of social justice and reconciliation.